A smarter path to safety: how AI can prevent the next workplace tragedy - Ebrahimi, Mohammad Hossein; Jamshidi Rastani, Mahdi; Barkhordari, Abdullah (Shahroud Journal of Medical Sciences, 2025)
The Bandar Abbas explosion: a stark reminder of safety and health gapsOn April 25, 2025, a devastating explosion rocked the Shahid Rajaee Port in Bandar Abbas, resulting in multiple fatalities and over 100 injuries. Preliminary investigations suggest that the accident may have stemmed from non-compliance with hazardous materials storage protocols and inadequate segregation of dangerous substances (1). This tragedy echoes historical industrial disasters such as the Tabas coal mine collapse and the Damghan mining accident—each serving as a stark reminder of the critical importance of proactive hazard identification, comprehensive risk assessment, and the implementation of robust control measures in occupational environments. When hazards remain unidentified or mitigation strategies are absent, the outcomes are often catastrophic and irreversible.